IMPLEMENTASI KEBIJAKAN SISTEM ZONASI PENERIMAAN PESERTA DIDIK BARU PADA JENJANG SEKOLAH MENENGAH ATAS ATAU SEDERAJAT DI KABUPATEN PANDEGLANG - Wildan Mutaqin; Abdul Rahman (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study is motivated by the persistent inequality in implementing the zoning policy for New Student Admissions (PPDB) in Pandeglang Regency. The policy, designed to ensure equitable access and quality in education, has not been fully effective due to several field constraints. The main issues identified include uneven communication between implementers and the public, limited human resources and educational facilities, weak commitment from policy implementers, and a bureaucratic structure that remains overly centralized. This research aims to analyze the implementation of the zoning policy based on George C. Edward III’s four variables of policy implementation: communication, resources, disposition, and bureaucratic structure. The study employs a descriptive qualitative method with data collected through interviews, observations, and documentation involving the Education Office, school principals, and teachers from several public high schools in Pandeglang Regency. The findings reveal that the implementation of the zoning policy has not been optimal. The primary obstacles lie in uneven communication and policy dissemination, limited human and infrastructural resources, and a highly centralized bureaucracy. The study concludes that improving policy literacy, equalizing educational facilities, and involving communities in policy evaluation are essential to achieving equitable and just educational access.